PELATIHAN MANAJEMEN PRODUK DENGAN PENDEKATAN KOMUNIKASI BISNIS BAGI UMKM DESA KARANGMULYA UNTUK MENINGKATKAN LABA - Nurnaja, Feby; Mulyanti, Kurniawati; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2024)
Business communication is one of the factors that can maintain the continuity of a business, both multinational and micro, small and medium enterprises. MSMEs must continue to struggle to face an increasingly competitive market in one way is to communicate their business to consumers and potential customers. Therefore, business communication must be improved to increase profits and for the business to survive in the long run. Through qualitative approaches such as observation and interviews with business actors. Observations show that there is a lack of business communication carried out by MSMEs. In the community service program to overcome these problems, the author uses the implementation method by providing socialization and training on the importance of communication business and training on delivering communication to consumers and prospective customers with a business communication form approach. With this program, it is expected that business actors can implement good business communication to consumers and potential customers. The results obtained can benefit the local community and MSME players and can add insight into business communication.